GmNAC81 Inversely Modulates Leaf Senescence and Drought Tolerance - Ferreira, Dalton O.; Fraga, Otto T.; Pimenta, Maiana R.; Caetano, Hanna D. N.; Machado, João Paulo B.; Carpinetti, Paola A.; Brustolini, Otávio J. B.; Quadros, Iana P. S.; Reis, Pedro A. B.; Fontes, Elizabeth P. B. (Frontiers in Genetics, 2020)
Glycine max NAC81 (GmNAC81) is a downstream effector of the DCD/NRP-mediated cell death signaling, which interacts with GmNAC30 to fully induce the caspase 1-like vacuolar processing enzyme (VPE) expression, the executioner of the cell death program. GmNAC81 has been previously shown to positively modulate leaf senescence via the NRP/GmNAC81/VPE signaling module. Here, we examined the transcriptome induced by GmNAC81 overexpression and leaf senescence and showed that GmNAC81 further modulates leaf senescence by regulating an extensive repertoire of functionally characterized senescence-associated genes (SAGs). Because the NRP/GmNAC81/VPE signaling circuit also relays stress-induced cell death signals, we examined the effect of GmNAC81 overexpression in drought responses. Enhanced GmNAC81 expression in the transgenic lines increased sensitivity to water deprivation. Under progressive drought, the GmNAC81-overexpressing lines displayed severe leaf wilting, a larger and faster decline in leaf Ψw, relative water content (RWC), photosynthesis rate, stomatal conductance, and transpiration rate, in addition to higher Ci/Ca and lower Fm/Fv ratios compared to the BR16 control line. Collectively, these results indicate that the photosynthetic activity and apparatus were more affected by drought in the transgenic lines. Consistent with hypersensitivity to drought, chlorophyll loss, and lipid peroxidation were higher in the GmNAC81-overexpressing lines than in BR16 under dehydration. In addition to inducing VPE expression, GmNAC81 overexpression uncovered the regulation of typical drought-responsive genes. In particular, key regulators and effectors of ABA signaling were suppressed by GmNAC81 overexpression. These results suggest that GmNAC81 may negatively control drought tolerance not only via VPE activation but also via suppression of ABA signaling.